Pengaruh Brand Image Terhadap Keputusan Pasien Rawat Inap Untuk Memanfaatkan Pelayanan Kesehatan Di RS DR. Tadjuddin Chalid Makassar Tahun 2021 - Karmita; Arman; Muh. Khidri Alwi (Program Pascasarjana Universitas Muslim Indonesia, 2021)
Background: Brands reflect customer perceptions and feelings regrading product attributers and performance, brand names and companies associated with the brand associated. In utilizing health services, customers are built by several considerations, one of which influences the customer’s consideration of the high brand image of a hospital. The purpose of this study is to analyze the effect of corporate identity, physical environment, contact personelle, and service offering on the interesting of community to utilize service at Dr. Tadjuddin Chalid Hospital Makassar. Methods: This is a quantitative research that uses cross sectional study method. Respondents in this study are 78 inpatients of Dr. Tadjuddin Chalid Hospital Makassar, determined by using simple random sampling technique. Results: Based on the the chi-square statistical test results, corporate identity, physical environment, contact personelle, and service offering an influence on patient decision using health service at Dr. Tadjuddin Chalid Hospital Makassar with the value of all variables, namely p=0.000 < p=0.05. Conclusion: (1) There was influenced between corporate identity with patient decision using health service at Dr. Tadjuddin Chalid Hospital Makassar; (2) There was influenced between physical environment with patient decision using health service at Dr. Tadjuddin Chalid Hospital Makassar; (3) There was influenced between contact personelle with patient decision using health service at Dr. Tadjuddin Chalid Hospital Makassar; and (4) There was influenced between service offering with patient decision using health service at Dr. Tadjuddin Chalid Hospital Makassar.